The problem situation of teaching-learning management of teachers in the subject of history in the 5th gradeat the high school of demonstrationacademic year2022-2023 - PHOUTSADY, Phetsamone; MALAYSAN, Pany; BOUATHAVONG, Dalasin (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research is about research the problem situation of teaching-learning management of teachers in the subject of history in the 5th gradeat the high school of demonstration academic year 2022-2023. The aim is to study the teaching-learning situation of the teachers in the history subject at the 5th gradeat the high school academic year2022-2023. This study used a quantitative method, Sample group used in 5th grade studentswhich has a total of 25 people, The instrument used in the research is a questionnaire, Statistics applicable to mean and standard deviation data analysis is defined using data analysis results as follows: The teaching-learning situation of the teacher in the subject of historyin the 5thgradeat the high school of demonstration academic year 2022-2023 Overall, all aspects are in good conditionwhich has an average value equal to ( =3.52) and the standard deviation is equal to (SD=0.43). When separated according to the surface, it is expressed as the introduction skills of the teacher's lesson overall and separate items are at a good levelwhich is the mean, standard deviation is equal to ( =3.88; SD=0.04) Teacher's activity management skillswhich is the mean, standard deviation is equal to ​( =3.32; SD=0.10). Teacher's questioning skillswhich is the mean, standard deviation is equal to ​( =3.34; SD=0.91). Skills in using teaching and learning mediawhich is the mean, standard deviation is equal to​ ( =3.42; SD=0.55). Summarizing and evaluating skillswhich is the mean, standard deviation is equal to ( =3.63; SD=0.53).